Pengaruh Kepemimpinan Profetik Terhadap Etos Kerja Guru PAI dan Pembentukan Karakter Islami Siswa di Sekolah Islam Terpadu Kota Mataram - Hartawan; Adi Fadli; Ribahan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the influence of prophetic leadership on: 1) the work ethic of PAI teachers, 2) the formation of students' Islamic character, and 3) both simultaneously in Integrated Islamic Schools (SIT) in Mataram City. The research employed a quantitative approach with an ex post facto design. The sample consisted of 80 respondents, including principals, PAI teachers, and students. The instrument was a questionnaire based on indicators of prophetic leadership (sidiq, amanah, tabligh, fathanah), work ethic, and Islamic character. Data were collected through surveys, observation, and documentation, then analyzed using multivariate regression tests. The results showed: (1) there is a significant influence of prophetic leadership on PAI teachers' work ethic (significance 0.001); (2) there is a significant influence on the formation of students' Islamic character (0.011); and (3) there is a significant simultaneous influence on both variables. The implication is that prophetic leadership, based on prophetic role modeling, plays a strategic role in improving teacher professionalism and strengthening students' Islamic character, making it worthy as a strategic leadership model in Islamic educational institutions